Medicines and intellectual property: 10 years of the WHO global strategy - Germán Velásquez (South Centre, 2019)
The negotiations of the Intergovernmental Working Group on Public Health, Innovation and Intellectual Property (IGWG) (2006-2008), undertaken by the Member States of the World Health Organization (WHO), were the result of a deadlock in the 2006 World Health Assembly where the Member States were unable to reach an agreement on what to do with the 60 recommendations in the report on Public Health, Innovation and Intellectual Property submitted to the Assembly in the same year by a group of experts designated by the Director-General of the WHO. The result of these negotiations was the Global Strategy and Plan of Action on Public Health, Innovation and Intellectual Property (GSPOA) that was approved by the World Health Assembly in 2008. One of the objectives of the IGWG's Global Strategy and Plan of Action was to substantially reform the pharmaceutical innovation system in view of its failure to produce affordable medicines for diseases that affect the greater part of the world's population living in developing countries. The intellectual property (IP) rights imposed by the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and the trade agreements could become some of the main obstacles to accessing medicines. The GSPOA made a critical analysis of this reality and opened the door to the search for new solutions to this problem. Ten years after the approval of the GSPOA, the results are uncertain and poor.
Keywords: 300; Arzneimittel; Immaterialgüterrechte; Gesundheitsversorgung; Menschenrechte; Internationale Organisation; Welt